Characterization and Classification of Sugarcane Growing Soils in Southern Agro-Climatic Zone: A Case Study in Eastern Mandals of Chittoor District in Andhra Pradesh - A. Ramakrishna Rao, P.A. Visalakshi Devi, M.V.S. Naidu (Journal of the Indian Society of Soil Science, 2005)
Eleven typical pedons namely, KMV Palli (P1), RKVB Peta (P2), Karvetinagaram (P3), Velavadi (P4), Natteri (P5), Nagalapuram (P6), Brahmanakalva (P7), Kasturkandriga (P8), Vemur (P9), Perumallapalli West (P10) and Perumallapalli East (P11) representing major land forms of plains and uplands were studied in sugarcane growing areas of Chittoor district in Andhra Pradesh. These soils developed from weathered gneiss, alluvium and weathered gneiss mixed with kankar parent material were studied for their morphological characteristics, physical and physicochemical properties and soil genesis. These soils were near neutral (6.90) to strongly alkaline (9.61) in reaction, non-saline (0.01 to 0.41dS m-1), shallow (P1), deep (P5) to very deep (P2, P3, P4, P6, P7, P8, P9, P10 and P11), and had isohyperthermic temperature and Ustic soil moisture regime. Texture, organic carbon (OC), cation exchange capacity (CEC) and base-saturation ranged from sand to clay loam in surface and sub-surface, 0.1 to 6.2 g kg-1, 1.05 to 33.34 cmol(p+)kg-1 and 54.9 to 93.35 per cent, respectively. Soils were low to medium in available N, low to high in available P and K and high in available S. The DTPA-extractable Zn was sufficient in surface horizons and deficient in sub-surface horizons in all pedons, except P7 wherein it was deficient and the soils were deficient in DTPA-extractable Fe and sufficient in Cu and Mn. These pedons were classified as Typic Ustorthents (P1, P5 and P6), Ultic Haplustalfs (P2 and P3), Typic Haplustalfs (P4 and P9), Vertic Haplustept (P7 and P11), Typic Ustipsamment (P8) and Typic Ustifluvent (P10).